High strain in Bi0.5Na0.5TiO3-based relaxors by adding two modifiers featuring with morphotropic phase boundary. (September 2022) - Shi, Peng; Li, Tangyuan; Zhu, Xiaopei; Liu, Wenyuan; Liu, Qida; Yang, Bian; Wang, Xiangjian; Kang, Ruirui; Yang, Sen; Lou, Xiaojie
Abstract: The electric field-induced strain in lead-free piezoceramics is generally limited to less than 0.4%, which hinders their practical applications such as actuator. Herein we report a new composition of 0.94Bi0.5 Na0.5 TiO3 -0.06Ba0.85 Ca0.15 Ti0.9 Zr0.1 O3 - x Li0.06 (K0.5 Na0.5 )0.94 NbO3 (BNT-BCZT- x LKNN) ceramics by adding two modifiers (i.e., Li0.06 (K0.5 Na0.5 )0.94 NbO3 and Ba0.85 Ca0.15 Ti0.9 Zr0.1 O3 ) featuring with a morphotropic phase boundary (MPB) into the Bi0.5 Na0.5 TiO3 system. The BNT-BCZT-0.02LKNN shows a high strain of 0.5% as well as a strain-electric field ratio ( S max / E max ) of 625 pm/V, which is one of the best performances compared with reported lead-free piezoceramics. Rietveld refinement and microstructure analysis confirmed the existence of tetragonal ( P 4bm) and rhombohedral ( R 3c) phases, and a small part of ferroelectric domains embedded into relaxors according to the PFM, both facilitating the relaxor-to-ferroelectric transformation under an external electric field. As a result, a high strain is obtained in the BNT-BCZT-LKNN system. Our work provides an effective strategy for designing novel lead-free materials with high strain. Graphical abstract: Image, graphical abstract Fig. in abstract (a) P-E loops, (b) S-E curves, and (c) J-E curves for x  = 0, x  = 0.02, x  = 0.04 samples. (d) S and d 33 * for all samples.